Age Effects on Distraction in a Visual Task Requiring Fast Reactions: An Event-Related Potential Study - Kojouharova, Petia; Gaál, Zsófia Anna; Nagy, Boglárka; Czigler, István (Frontiers in Aging Neuroscience, 2020)
We investigated the effects of distractors in older and younger participants in choice and simple reaction time tasks with concurrent registration of event-related potentials. In the task the participants had to prevent a disc from falling into a bin after a color or luminosity change (target stimuli). Infrequently, task-irrelevant stimuli (schematic faces or threatening objects) were superimposed on the target stimuli (distractors), or the bin disappeared which required no response (Nogo trials). Reaction time was delayed to the distractors, but this effect was similar in the two age groups. As a robust age-related difference, in the older group a large anterior positivity and posterior negativity emerged to the distractors within the 100-200 ms post-stimulus range, and these components were larger for schematic faces than for threatening objects. sLORETA localized the age-specific effect to the ventral stream of the visual system and to anterior structures considered as parts of the executive system. The Nogo stimuli elicited a late positivity (Nogo P3) with longer latency in the older group. We interpreted the age-related differences as decreased but compensated resistance to task-irrelevant change of the target stimuli.